Lateralized Tinnitus Studied With Functional Magnetic Resonance Imaging: Abnormal Inferior Colliculus Activation - Melcher, J. R; Sigalovsky, I. S; Guinan, J. J., Jr; Levine, R. A (Journal of neurophysiology, 2000)
1 Eaton-Peabody Laboratory, Massachusetts Eye and Ear Infirmary, Boston 02114;   2 Department of Otology and Laryngology, Harvard Medical School, Boston 02114; 3 Speech and Hearing Sciences Program, Harvard-MIT Division of Health Sciences and Technology, Massachusetts Institute of Technology, Cambridge 02139; and 4 Neurology Service, Massachusetts General Hospital, Boston, Massachusetts 02114 Melcher, J. R., I. S. Sigalovsky, J. J. Guinan Jr., and R. A. Levine. Lateralized Tinnitus Studied With Functional Magnetic Resonance Imaging: Abnormal Inferior Colliculus Activation. J. Neurophysiol. 83: 1058-1072, 2000. Tinnitus, the perception of sound in the absence of external stimuli, is a common and often disturbing symptom that is not understood physiologically. This paper presents an approach for using functional magnetic resonance imaging (fMRI) to investigate the physiology of tinnitus and demonstrates that the approach is effective in revealing tinnitus-related abnormalities in brain function. Our approach as applied here included 1 ) using a masking noise stimulus to change tinnitus loudness and examining the inferior colliculus (IC) for corresponding changes in activity, 2 ) separately considering subpopulations with particular tinnitus characteristics, in this case tinnitus lateralized to one ear, 3 ) controlling for intersubject differences in hearing loss by considering only subjects with normal or near-normal audiograms, and 4 ) tailoring the experimental design to the characteristics of the tinnitus subpopulation under study. For lateralized tinnitus subjects, we hypothesized that sound-evoked activation would be abnormally asymmetric because of the asymmetry of the tinnitus percept. This was tested using two reference groups for comparison: nontinnitus subjects and nonlateralized tinnitus subjects. Binaural noise produced abnormally asymmetric IC activation in every lateralized tinnitus subject ( n  = 4). In reference subjects ( n  = 9), activation (i.e., percent change in image signal) in the right versus left IC did not differ significantly. Compared with reference subjects, lateralized tinnitus subjects showed abnormally low percent signal change in the IC contralateral, but not ipsilateral, to the tinnitus percept. Consequently, activation asymmetry (i.e., the ratio of percent signal change in the IC ipsilateral versus contralateral to the tinnitus percept) was significantly greater in lateralized tinnitus subjects as compared with reference subjects. Monaural noise also produced abnormally asymmetric IC activation in lateralized tinnitus subjects. Two possible models are presented to explain why IC activation was abnormally low contralateral to the tinnitus percept in lateralized tinnitus subjects. Both assume that the percept is associated with abnormally high ("tinnitus-related") neural activity in the contralateral IC. Additionally, they assume that either 1 ) additional activity evoked by sound was limited by saturation or 2 ) sound stimulation reduced the level of tinnitus-related activity as it reduced the loudness of (i.e., masked) the tinnitus percept. In summary, this work demonstrates that fMRI can provide objective measures of lateralized tinnitus and tinnitus-related activation can be interpreted at a neural level.